What Nephrologists Should Know about the Use of Continuous Glucose Monitoring in Type 2 Diabetes Mellitus Patients on Chronic Hemodialysis - Faiza Lamine; Menno Pruijm; Virginie Bahon; Anne Zanchi (Kidney and Dialysis, 2022)
Patients with type 2 diabetes (T2D) and end-stage kidney disease (ESKD) on renal replacement therapy represent a specific population with high morbidity and mortality, an increased risk of hypoglycemic episodes and large intra- and interdialysis glycemic variability. Antidiabetic treatment adjustment is therefore challenging, especially in insulin-treated patients. Continuous glucose monitoring (CGM) is increasingly proposed to T2D patients on hemodialysis (HD), although data regarding flash monitoring systems (FMSs) and real-time CGM (rtCGM) in HD patients are limited. Small CGM pilot studies of a short duration demonstrated improvements in glycemic control and decreased hypoglycemic events, despite a lower accuracy of CGM as compared to capillary blood glucose. Moreover, CGM–drug interactions with vitamin C, mannitol and paracetamol can occur in HD diabetic patients and need further study. Despite these shortcomings, professional CGM has the potential to become an integral part of glucose monitoring of HD patients treated with insulin. Personal CGM prescriptions can especially be useful in highly selected, motivated T2D HD patients on multiple daily insulin injections or experiencing frequent hypoglycemia with preserved diabetes self-management abilities or in whom diabetes is fully managed by medical providers. A close collaboration between the clinical staff working on HD units and diabetology teams, and ongoing patient education, are mandatory for optimal use of CGM.